Macrofauna community of the cold seep area at Site F, South China Sea - Wang, Haining; Wang, Xiaocheng; Cao, Lei; Zhong, Zhaoshan; Luan, Zhendong; Li, Chaolun (Frontiers in Marine Science, 2023)
Cold seep is one of the typical deep-sea chemical-energy ecosystems, which is a hotspot for studying the special life process and biogeochemical cycle in the deep sea. Macrofauna, which is one of the most important components at cold seep ecosystem, have not been well studied. We examined macrofauna community at site F through analyses of images collected by Imaging and laser Profiling system in 2016 and biological samples collected by TV grab and ROV in 2020 and 2021. In total, 41 species were found and identified. The total number of macrofauna at site F (20,000 m2) can reach 252,943 individuals and the biomass can reach 726.15 kg dry weight. As the dominant species, the highest density of G. platifrons and S. crosnieri reach 629 and 396 ind./m2, respectively. The comparisons of different stations revealed that the diversity and density, even the biomass of dominant species, were much higher in the south than in north at site F in 2020. Correlation analysis showed methane had a positive effect on macrofauna density. Compared with S. crosnieri, G. platifrons seem to be better to adapt the harsh cold seep environment. Methane consumption rates of the dominant species show that macrofauna is important in influencing the seafloor methane fluxes. Our results provide valuable insights into ecology, community structure and interaction between biotic and environment at site F cold seep.